A fast online load identification algorithm based on V-I characteristics of high-frequency data under user operational constraints. (1st December 2019) - Wu, Xin; Jiao, Dian; Liang, Kaixin; Han, Xiao
Abstract: Non-intrusive load monitoring is an effective way for the power grid to obtain the power consumption on the user side. High-frequency data acquisition mode can provide more load information with a large amount of data, which is suitable for load online identification. However, high accuracy and real-time performance are required. In this regard, a fast online identification algorithm based on V-I characteristics of high-frequency is studied: According to the principle of constant capacitive and inductive characteristic of electrical appliance, under same voltage setting, the periodic current of previous switching appliance-when it is running stably-can be calculated by steady periodic current obtained each time before transient state with one-dimensional addition/subtraction. Then, the target function can be further constrained by incorporating residents' habits, thus narrowing down the scope of possible combinations of the electrical devices that may have switched. Finally, the load states can be determined through solving the optimized function under operational constraints. This study can extract accurate and stable load currents to identify the switching load, and effectively determine the on/off time of each appliance in a short period of time. Experiments on the public BLUED dataset and laboratory data verify the effectiveness of the algorithm together. Highlights: Identification results are transmitted to the grid side for storage and analysis. The optimization model based on GA ensures identification process within seconds. V-I Characteristics based identification method retain abundant load information. NILM can obtain the power consumption and proportion of each load.